Chemoresistance and Metastasis in Breast Cancer Molecular Mechanisms and Novel Clinical Strategies - Cao, Jun; Zhang, Mengdi; Wang, Bin; Zhang, Long; Zhou, Fangfang; Fang, Meiyu (Frontiers in Oncology, 2021)
Breast cancer is the most common malignant tumor in females worldwide. Chemotherapy is the standard breast cancer treatment; however, chemoresistance is often seen in patients with metastatic breast cancer. Owing to high heterogeneity, the mechanisms of breast cancer chemoresistance and metastasis have not been fully investigated. The possible molecular mechanisms of chemoresistance in breast cancer include efflux transporters, signaling pathways, non-coding RNAs, and cancer stem cells. However, to overcome this hurdle, the use of novel clinical strategies such as drug carriers, immunotherapy, and autophagy regulation, are being investigated. The goal of this review is to summarize the current data about the molecular mechanisms of breast cancer chemoresistance and the novel clinical strategies; thus, providing a useful clinical tool to explore optimal treatment for breast cancer.